Aggravated Sanctions in Cases of Sexual Violence Against Persons with Disabilities: A Comparative Study of Positive Law and Islamic Criminal Law - Soni Askar Sinaga; Syaddan Dintara Lubis (Al-Risalah Jurnal Ilmu Syariah dan Hukum, 2025)
The phenomenon of sexual violence against persons with disabilities reveals a pattern of double vulnerability that demands stronger legal protection. This study aims to analyze and compare the aggravating sanctions imposed on perpetrators of sexual violence against persons with disabilities in both positive criminal law and Islamic criminal law. Employing a normative juridical method with a comparative approach, the research focuses on Law Number 12 of 2022 concerning Sexual Violence Crimes (UU TPKS) and the principles of Islamic criminal law related to jarīmah ta‘zīr and maqāṣid al-sharī‘ah. The findings indicate that positive criminal law explicitly provides for a one-third sentence enhancement when the victim is a person with a disability. However, in practice, the application of this provision remains inconsistent due to limited awareness among law enforcement officials. In contrast, Islamic criminal law, while not specifying persons with disabilities, allows for aggravated sanctions based on moral considerations and the imperative to protect vulnerable groups. Both legal systems share a common orientation toward victim protection and the realization of substantive justice. The originality of this study lies in its cross-system analysis that integrates normative legal review with theological perspectives on vulnerability. The research implies a need for stronger synergy between legal frameworks and judicial practice, advocating for enhanced training, clearer implementation guidelines, and the incorporation of Islamic legal principles to reinforce protections for persons with disabilities. Such integration could lead to a more inclusive and just criminal justice system.